2014
DOI: 10.1002/dmrr.2551
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus is associated with early chronic venous disorder of the lower extremities in Chinese patients with cardiometabolic risk factors

Abstract: Female subjects with cardiometabolic risk factors or female diabetic patients face a greater risk of early chronic venous disorder than do male subjects. Diabetic patients with early chronic venous disorder had more serious macrovascular complications than did the controls, and the early venous function was found to be correlated with the blood glucose level and triglyceride status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…general complications that inflict important health care costs and reduce the patient's quality of life (16). One recent study demonstrated that female subjects with cardiometabolic risk factors or female diabetic patients are at greater risk of developing early chronic venous disorder than the male subjects (17), nevertheless the factors that determine whether a given patient will progress from mild to more severe form of CVD remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…general complications that inflict important health care costs and reduce the patient's quality of life (16). One recent study demonstrated that female subjects with cardiometabolic risk factors or female diabetic patients are at greater risk of developing early chronic venous disorder than the male subjects (17), nevertheless the factors that determine whether a given patient will progress from mild to more severe form of CVD remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Many "Civilization Diseases" such as metabolic syndrome, coronary artery disease (CAD), hypertension, diabetes mellitus (DM), allergic diseases, non-alcoholic fatty liver disease, psoriasis, gout, etc., have similar metabolic disorders such as hyperlipidemia/dyslipidemia, hyperglycemia, hyperinsulinemia, hypercortisolemia, hyperuricemia, microalbuminuria, which can be signs of AS [ 4 , 5 ]. In this case, the problem of clinical solution AS and its clinical species are socially significant [ 6 ].…”
Section: Introductionmentioning
confidence: 99%